GGPS1 Mutations Cause Muscular Dystrophy/Hearing Loss/Ovarian Insufficiency Syndrome. Issue 2 (18th June 2020) - Foley, A. Reghan; Zou, Yaqun; Dunford, James E.; Rooney, Jachinta; Chandra, Goutam; Xiong, Hui; Straub, Volker; Voit, Thomas; Romero, Norma; Donkervoort, Sandra; Hu, Ying; Markello, Thomas; et al.
Abstract : Objective: A hitherto undescribed phenotype of early onset muscular dystrophy associated with sensorineural hearing loss and primary ovarian insufficiency was initially identified in 2 siblings and in subsequent patients with a similar constellation of findings. The goal of this study was to understand the genetic and molecular etiology of this condition. Methods: We applied whole exome sequencing (WES) superimposed on shared haplotype regions to identify the initial biallelic variants in GGPS1 followed by GGPS1 Sanger sequencing or WES in 5 additional families with the same phenotype. Molecular modeling, biochemical analysis, laser membrane injury assay, and the generation of a Y259C knock‐in mouse were done. Results: A total of 11 patients in 6 families carrying 5 different biallelic pathogenic variants in specific domains of GGPS1 were identified. GGPS1 encodes geranylgeranyl diphosphate synthase in the mevalonate/isoprenoid pathway, which catalyzes the synthesis of geranylgeranyl pyrophosphate, the lipid precursor of geranylgeranylated proteins including small guanosine triphosphatases. In addition to proximal weakness, all but one patient presented with congenital sensorineural hearing loss, and all postpubertal females had primary ovarian insufficiency. Muscle histology was dystrophic, with ultrastructural evidence of autophagic material and large mitochondria in the most severe cases. There was delayed membrane healing after laser injury in patient‐derived myogenic cells, and a knock‐in mouse of one of the mutations (Y259C) resulted in prenatal lethality. Interpretation: The identification of specific GGPS1 mutations defines the cause of a unique form of muscular dystrophy with hearing loss and ovarian insufficiency and points to a novel pathway for this clinical constellation. ANN NEUROL 2020;88:332–347.